Educational Reforms and Implementation of Student-Centered Active Learning in Science at Secondary and University Levels in Qatar - Qureshi, S.; Bradley, K.; Vishnumolakala, Venkat Rao; Treagust, David; Southam, Daniel; Mocerino, Mauro; Ojeil, J. (International Council of Associations for Science Education (ICASE), 2016)
The Qatari government has made significant changes in the organization and staffing of schools over the past decade in an effort to improve the academic performance of school-aged citizens. Of interest is the need to encourage teachers to move from a didactic teacher-led mode of instruction to one that is more student-centred, but also teacher-guided, which encourages the development of critical thinking, problem solving, inquiry, and investigative skills. In this article, we discuss past and current educational changes and developments in Qatar with an emphasis on an initiative in chemistry that explored the utility and cultural transferability of student inquiry learning approaches to improve student conceptual understanding as well as their attitudes and self-efficacy. Based on the current activities described in this article, we argue that the developments and commitment to educational reform in Qatar can act as a guide for other nations that wish to move from a didactic teaching to a more student-centred approach.